The EU Budget and the Role of Public Goods - Antonia Díaz (CESifo Forum, 2021)
This paper argues that investing in public institutions and goods are the best tool for shielding the economy against events similar to Covid-19 because private agents cannot foresee extremely unlikely events and there are markets where informational problems are pervasive. This is even more true in a confederation such as the European Union, where the right mix of public transfers and public goods is critical in minimizing incentive problems related to consolidating the single market and European integration. The Multiannual Financial Framework 2021-27 and the Fund Next Generation are steps in this direction.
Keywords: 330